MEMBUKA LAYAR IMPIAN: BUDAYA POSKOLONIAL DALAM FILM INDONESIA ERA 2000-AN - , Ikwan Setiawan, Prof. Dr. Faruk ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study discusses the representation of postcolonial culture in Indonesian filmsâ narratives in the 2000s with viewpoint on: (1) the representations of âthe modernâ and âthe traditionalâ in filmic narrative structures